Assessment of medication review among pharmacy professionals in the UAE: A cross-sectional study on knowledge, attitudes, practices, and barriers - Rizah Anwar Assadi; Semira Beshir; Omaimah Toufiq; Selma Benwahmane Castell; Mariam Jihad Diab; Shabaz Mohiuddin Gulam (PLoS ONE, 2025)
Background Medication reviews are vital for optimizing patient care and resolving drug-related problems, with pharmacists playing a key role. Understanding pharmacists’ knowledge, attitudes, perceived barriers, and practices regarding medication reviews in the UAE is crucial for enhancing medication safety. Aim To assess the knowledge, attitudes, perceived barriers, and practices of pharmacy professionals in the UAE concerning medication reviews. Methods An online cross-sectional survey was distributed to licensed pharmacists in the UAE with at least a bachelor’s degree. The survey collected data on demographics, knowledge, attitudes, perceived barriers, and practices related to medication reviews. Descriptive statistics, Mann-Whitney U tests, Kruskal-Wallis H tests, and Spearman’s rank correlation were used for data analysis. Results Of 426 pharmacists approached, 421 responded (98.8%). Most agreed that medication reviews should be pharmacist-led (99.5%) and include comprehensive patient profiles (99.0%). Awareness was high for prescription reviews (94.3%) but low for Pharmaceutical Care Network Europe classifications (4.3%). Positive attitudes were widespread (98.8%), and major barriers included time constraints (83.6%) and workload (76.7%). Around 73% conducted medication reviews, but over half did not use standardized tools. Gender differences were found in knowledge (p = 0.003) and attitudes (p = 0.007). Conclusion Pharmacists in the UAE have positive attitudes toward medication reviews but face barriers, particularly time constraints and workload. Enhanced training is needed to address these issues and improve patient outcomes.